Ciliates and the Rare Biosphere: A Review. (2nd June 2014) - Dunthorn, Micah; Stoeck, Thorsten; Clamp, John; Warren, Alan; Mahé, Frédéric
Abstract Here we provide a brief review of the rare biosphere from the perspective of ciliates and other microbial eukaryotes. We trace research on rarity from its lack of much in‐depth focus in morphological and Sanger sequencing projects, to its central importance in analyses using high throughput sequencing strategies. The problem that the rare biosphere is potentially comprised of mostly errors is then discussed in the light of asking community‐comparative, novel‐diversity, and ecosystem‐functioning questions.